Alienation Theory in Comparative Perspective: Marx’s Economic and Philosophic Manuscripts of 1844 and Marcuse’s One-Dimensional Man - Wang, Nan (International Journal of Social Sciences and Public Administration, 2025)
In Economic and Philosophic Manuscripts of 1844 (hereafter Manuscripts), Karl Marx critiques alienated labor and private ownership under capitalism through his analysis of the harsh conditions faced by workers. Over a century later, Herbert Marcuse, building on Marx’s theory of alienated labor and responding to new developments in capitalism, proposes the concept of technological alienation. He argues that science and technology have evolved into novel forms of social control. While Marcuse’s theory of technological alienation inherits Marx’s framework, significant divergences inevitably emerge due to the century-long gap between their historical contexts and the distinct socio-economic realities they addressed.